HEATHER MACNEIL and TERRY EASTWOOD, eds., Currents of Archival Thinking, 2nd ed. - Dorey, Jonathan (Archivaria, 2017)
Currents of Archival Thinking, 2nd ed. HEATHER MACNEIL and TERRY EASTWOOD, eds. Santa Barbara, CA: Libraries Unlimited, 2017. xiii, 398 pp. ISBN 978-1-4408-3908-5.